2002
DOI: 10.1021/jp020537u
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bond Rearrangements and Interconversions of H+(CH3OH)4H2O Cluster Isomers

Abstract: Rearrangement of hydrogen bonds in the protonated methanol-water cluster ion H + (CH 3 OH) 4 H 2 O is analyzed. The analysis, based on ab initio calculations performed at the B3LYP/aug-cc-pVTZ//6-31+G* and MP4/ 6-311+G*//B3LYP/6-31+G* levels of computation, provides information about potential minima, transition states, and pathways for the hydrogen bond rearrangement processes. Results of the analysis are compared systematically to the experimental measurements for H + (CH 3 OH) 4 H 2 O, where two distinct ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 37 publications
0
46
1
1
Order By: Relevance
“…The band gaps calculated in this work indicate that all considered phases pertain to low-gap semiconductors. This disagrees with the results of previous DFT calculations [34,36,38,43] of 1T-o phases. The one of the possible explanation of appearance of nonzero gap between the valence and conductance states is the type of Hamiltonian.…”
Section: Bulk Phasescontrasting
confidence: 99%
See 1 more Smart Citation
“…The band gaps calculated in this work indicate that all considered phases pertain to low-gap semiconductors. This disagrees with the results of previous DFT calculations [34,36,38,43] of 1T-o phases. The one of the possible explanation of appearance of nonzero gap between the valence and conductance states is the type of Hamiltonian.…”
Section: Bulk Phasescontrasting
confidence: 99%
“…The most of previous DFT calculations [34,36,38,43] have indicated that layered disulfides of titanium and zirconium should [36] 3.598 5.660 0.257 Semimetal PBEsol [36] 3.629 5.884 0.247 0.8 Experiment [d] 3.630 5.850 0.250 17.7 [c] 1.7 [37] [a] Ref. [38]; the relaxed cell constants have not been reported.…”
Section: Bulk Phasesmentioning
confidence: 99%
“…173 Both zeropoint energy and hydrogen bond cooperativity had a major impact on the location of the proton. 177 Studies of proton transfer using infrared laser spectroscopy preceded the investigations from the Lee group. The initial study focused on the sequential hydration of CH 3 OH 2 + with one to six waters.…”
Section: Synergymentioning
confidence: 99%
“…40 In this work, we apply a first-principles based multi-model method proposed by Nguyen et al to systematically search the local minimum structures of H + (MeOH) n so that conformational isomers within a H-bond morphological groups can be faithfully represented. 1,37,[49][50][51] The importance of the dispersion correction in the evaluation of the absolute binding energy has been demonstrated for the protonated methanol clusters by Fifen and co-workers. This level of theory and basis set were chosen because of its computational efficiency and reasonable accuracy.…”
mentioning
confidence: 99%